Traceable Dairy Supply Chain Implementation in Ukraine for Improved Export Potential - Chenyiman Lou; Roman Gorobec; Iuliia Samoilyk; Hana Trollman (Engineering Proceedings, 2023)
This research critically examines how the traceable dairy supply chain can be implemented in Ukraine to foster socio-economic outcomes, such as reduced food safety risk, higher product quality, improved shipping and storage, and greater consumer confidence for improved export potential [...]